Consenting to invasive contraceptives: an ethical analysis of adolescent decision-making authority for long-acting reversible contraception - Behmer Hansen, Rosemary Talbot (Journal of medical ethics, 2018)
Since USA constitutional precedent established in 1976, adolescents have increasingly been afforded the right to access contraception without first obtaining parental consent or authorisation. There is general agreement this ethically permissible. However, long-acting reversible contraception (LARC) methods have only recently been prescribed to the adolescent population. They are currently the most effective forms of contraception available and have high compliance and satisfaction rates. Yet unlike other contraceptives, LARCs are associated with special procedural risks because they must be inserted and removed by trained healthcare providers. It is unclear whether the unique invasive nature of LARC changes the traditional ethical calculus of permitting adolescent decision-making in the realm of contraception. To answer this question, we review the risk-benefit profile of adolescent LARC use. Traditional justifications for permitting adolescent contraception decision-making authority are then considered in the context of LARCs. Finally, analogous reasoning is used to evaluate potential differences between permitting adolescents to consent for LARC procedures versus for emergency and pregnancy termination procedures. Ultimately, we argue that the invasive nature of LARCs does not override adolescents’ unique and compelling need for safe and effective forms of contraception. In fact, LARCs may oftentimes be in the best interest of adolescent patients who wish to prevent unintended pregnancy. We advocate for the specific enumeration of adolescents’ ability to consent to both LARC insertion and removal procedures within state policies. Given the provider-dependent nature of LARCs and the stigma regarding adolescent sexuality, special political and procedural safeguards to protect adolescent autonomy are warranted.